Contingent factors and Sustainable Performance Measurement (SPM) practices of Malaysian electronics and electrical companies - Tze, San Ong; Boon, Heng Teh; Lee, Ah Suat (MDPI, 2019)
In the present world, there is a rapidly growing level of awareness of social and environmental activities. Consequently, a company’s profile is not substantiated purely in relation to financial issues, rather, a need for the inclusion of environmental and social perspectives arises. This is known as sustainable performance. Hence, there is a persistent need for the practice of sustainable performance measurements (SPMs). However, despite the implementation of sustainable performance in developed climes like Europe, the US and the UK, the relevance of sustainable performance is still at a low in developing societies such as Malaysia. The main purpose of this paper is to determine the critical success factors that are attributable to sustainable performance measurement practices for Malaysian electronics and electrical (E and E) companies, as their success is subject to intense scrutiny from their developed competitors, with respect to compliance with social and environmental regulations. A self-administered questionnaire survey was conducted on 217 E and E companies. The path analysis and test of the hypotheses were carried out through structural equation modelling. This study has successfully unveiled a comprehensive SPM model with unprecedented scope, stretching from factors to indicators of a SPM model for Malaysian E and E companies. The findings indicate that pressure from stakeholders and globalization are the driving forces for E and E companies to be more proactive in sustainable practices. In this context, stakeholders, especially policy makers, should play the leading political and social roles in encouraging the adoption of SPMs in developing nations. It must be noted that E and E companies are likely to transform their learning culture and technology in terms of working towards sustainable practices once they have realized the financial benefits of adopting SPMs. With these benefits, a compounding effect due to SPMs will be created among E and E companies, where excellent performance can be achieved continuously. A major limitation of this study is the adoption of the contingency theory, which is yet to have a wide application in this area of study. Meanwhile, future research can be longitudinal in nature in addition to focusing on non-profit organizations.